Alexandros, oder, Der Lügenprophet - Lucian, of Samosata. (Religions in the Graeco-Roman World, 1997)
Lucian's Alexander the False Prophet is the only literary testimony to a highly influential cult of the 'New Asclepios Glycon' which, as archaeological evidence continues to document, spread all over the eastern Mediterranean basin throughout the second and third centuries AD. This book offers an analysis of the complete manuscript tradition, a newly constituted text and a German translation. The extensive introduction deals with (1) the archaeological evidence, (2) the question of Lucian's historical reliability, (3) the reasons for Lucian's opposition to the oracle of Abonuteichos, (4) the institutions and the teaching of the cult at Abonuteichos. Furthermore, there is a commentary on all philological and historical questions and on those issues relevant to the history of religions. Lucian's Alexander is not one of his satirical bravuras, but a strikingly successful attempt at writing a work of contemporary history - a practical example of what the author himself has theoretically discussed in his work, How to Write History .